The Botanical Review - Stevenson, Dennis Wm.; Ambrose, Barbara A.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
For over half a century, The Botanical Review has been a leading international journal noted for its in-depth articles on a broad spectrum of botanical fields. Systematics, phytogeography, cladistics, evolution, physiology, ecology, morphology, paleobotany, and anatomy are but a few of the many subjects that have been covered. The Botanical Review draws together outstanding scientists in the field, synthesizes the current knowledge about a specific subject, and promotes the advancement of botany by indicating the gaps in our knowledge and providing new outlooks on the topic.
Keywords: Plant ecology; Plant science; Botany; Plant anatomy; Plant development; Plant systematics; Plant taxonomy; Plant Sciences; Plant Systematics/Taxonomy/Biogeography.; Plant Anatomy/Development.; Plant Physiology; Plant Ecology